Candidate pathogenicity factor/effector proteins of ‘Candidatus Phytoplasma solani’ modulate plant carbohydrate metabolism, accelerate the ascorbate–glutathione cycle, and induce autophagosomes - Dermastia, Marina; Tomaž, Špela; Strah, Rebeka; Lukan, Tjaša; Coll, Anna; Dušak, Barbara; Anžič, Barbara; Čepin, Timotej; Wienkoop, Stefanie; Kladnik, Aleš; Zagorščak, Maja; Riedle-Bauer, Monika; et al. (Frontiers in Plant Science, 2023)
The pathogenicity of intracellular plant pathogenic bacteria is associated with the action of pathogenicity factors/effectors, but their physiological roles for most phytoplasma species, including 'Candidiatus Phytoplasma solani' are unknown. Six putative pathogenicity factors/effectors from six different strains of 'Ca. P. solani' were selected by bioinformatics analysis. The way in which they manipulate the host cellular machinery was elucidated by analyzing Nicotiana benthamiana leaves after Agrobacterium-mediated transient transformation with the pathogenicity factor/effector constructs using confocal microscopy, pull-down and co-immunoprecipitation, and enzyme assays. Candidate pathogenicity factors/effectors were shown to modulate plant carbohydrate metabolism and the ascorbate-glutathione cycle, and to induce autophagosomes. PoStoSP06, PoStoSP13, and PoStoSP28 were localized in the nucleus and cytosol. The most active effector in the processes studied was PoStoSP06. PoStoSP18 was associated with an increase in phosphoglucomutase activity, whereas PoStoSP28, previously annotated as an antigenic membrane protein StAMP, specifically interacted with phosphoglucomutase. PoStoSP04 induced only the ascorbate-glutathione cycle along with other pathogenicity factors/effectors. Candidate pathogenicity factors/effectors were involved in reprogramming host carbohydrate metabolism in favor of phytoplasma own growth and infection. This is a provisional file, not the final typeset article They were specifically associated with three distinct metabolic pathways leading to fructose-6phosphate as an input substrate for glycolysis. The possible significance of autophagosome induction by PoStoSP28 is discussed.